An Empirical Investigation ofthe Effect of Workload and SOPs on Employees Work Morale - Emi Wakhyuni (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
The purpose of this study is to investigate the effect of workload, and Standard Operating Procedure (SOPs) on employees work morale. This study uses a quantitative approach that is an empirical study to collect, analyze, and display data. Population of this research is employees in PT. Sucofindo Medan Branch. The technique of determining sample used simple random sampling in which the subject of research used 50 percent. Therefore, The sample of this study amounted to 75 employees. The results of this study found that workload and Standard Operating Procedure have the significant impact on employees work morale in PT. Sucofindo Medan Branch simultaneously. Partially, the workload has not a significant effect on employees work morale in PT. Sucofindo Medan Branch. However, Standard Operating Procedure has a significant effect on employees work morale in PT. Sucofindo Medan Branch.The authors suggest to this company that they need to set up employee performance appraisal for the positions held. The company needs to prepare evaluation materials to improve work systems and procedures. The company is expected to consider the proposal to develop a real employee requirement plan related to the organization's workload. The company may apply for an employee mutation program from an excessive unit to a deficient unit.